Little Brown Bear won't go to school - Dyer, Jane (Boston : Little, Brown, 2002)
Little Brown Bear does not want to go to school, so he tries various jobs instead.
Keywords: Bears -- Juvenile fiction; Schools -- Juvenile fiction; Work -- Juvenile fiction